2014
DOI: 10.1186/1748-717x-9-113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of chemoradiation in patients with anal cancer - a retrospective analysis

Abstract: BackgroundConcurrent chemotherapy and radiation therapy is the preferred standard of care for patients with anal cancer. Several studies have suggested a benefit of intensity-modulated radiation therapy (IMRT) compared with 3D-conformal radiation (3D-CRT) regarding acute toxicity. This study evaluates outcome and toxicity of patients undergoing IMRT/Tomotherapy or 3D-CRT at our institution.MethodsA cohort of 105 anal cancer patients was treated with chemoradiation or radiation alone (16.2%) between January 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
3
27
1
Order By: Relevance
“…The study demonstrated that IMRT could reduce severe acute skin toxicity significantly (p<0.001) compared to 3D-CRT. No toxicity grade 4 was observed and G2/3 toxicity was reduced from 94.6% to 63.2%) [25]. No effect on overall survival, progression-free survival or on local control was observed.…”
Section: Discussionmentioning
confidence: 87%
“…The study demonstrated that IMRT could reduce severe acute skin toxicity significantly (p<0.001) compared to 3D-CRT. No toxicity grade 4 was observed and G2/3 toxicity was reduced from 94.6% to 63.2%) [25]. No effect on overall survival, progression-free survival or on local control was observed.…”
Section: Discussionmentioning
confidence: 87%
“…Thirteen publications incorporating 645 patients were identified, details of individual series are presented in Table 1 [27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…Definitions used incorporated criteria for grading the level of response; modality of assessment; and timing of assessment and there was heterogeneity in all of these aspects (Table S4). Twenty-two different definitions were used in the 23 studies; the most commonly used criteria for assessing the level of response was the Response Evaluation Criteria In Solid Tumours (RECIST), used in six studies [8,[21][22][23][24][25]. However only two of the studies using RECIST assessed response at the same time points [26,27].…”
Section: Disease Activitymentioning
confidence: 99%